ANALISIS RISIKO DEMAM BERDARAH TERHADAP LINGKUNGAN: MENINJAU DAMPAK DAN STRATEGI PENGELOLAAN - Permatasari, Desi (Jurnal Kesehatan, 2024)
Dengue fever (DB) is a global health problem that affects millions of people every year, especially in tropical and subtropical areas. This research aims to analyze the risk of dengue fever on the environment and management strategies. Through a mixed approach combining quantitative and qualitative methods, we investigated environmental factors influencing the spread of DB, the level of public awareness about prevention and control, and barriers to access to health services. The main findings show that environmental conditions that support the breeding of Aedes aegypti and Aedes albopictus mosquitoes are the main factors influencing the spread of DB. Low public awareness about this disease is also a serious challenge. We recommend strategic steps such as mosquito vector control, public education, environmental management, and increasing access to health services to reduce the burden of dengue fever. Collaboration between various parties is needed to face this challenge effectively